2018
DOI: 10.1007/s10661-018-6927-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of surface water quality by using Canadian Council of Ministers of the Environment Water Quality Index (CCME WQI) method and discriminant analysis method: a case study Coruh River Basin

Abstract: In this study, the water quality of the Coruh River Basin, which is located in the Eastern Black Sea Region of Turkey, was evaluated. The water quality data measurement results obtained by the State Hydraulic Works 26th Regional Directorate from four different sites over a course of 4 years between the years 2011 and 2014 in the Coruh River Basin were used as the data. In this study, the water quality was evaluated by using the Canadian Council of Ministers of the Environmental Water Quality Index (CCME WQI) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(47 citation statements)
references
References 30 publications
0
46
0
1
Order By: Relevance
“…It was focused to classify the suitability of river water for human use and identify the major pollutants present in the river. Globally, several water quality indices (WQI) have been developed for monitoring the surface WQ of freshwater bodies with respect to human use [16,17]. WQI is a concise and comprehensive method that expresses the river WQ or pollution status in a single number by aggregating the values of different physicochemical parameters [18].…”
Section: Introductionmentioning
confidence: 99%
“…It was focused to classify the suitability of river water for human use and identify the major pollutants present in the river. Globally, several water quality indices (WQI) have been developed for monitoring the surface WQ of freshwater bodies with respect to human use [16,17]. WQI is a concise and comprehensive method that expresses the river WQ or pollution status in a single number by aggregating the values of different physicochemical parameters [18].…”
Section: Introductionmentioning
confidence: 99%
“…Such monitoring programs generate a large amount of data with a complex structure and “hidden” knowledge concerning water quality. In many water quality assessment studies, multivariate statistical approaches are applied to retrieve important information concerning water quality management such as: (i) outlining similarity groups between water quality indicators and sampling sites [21,22,23,24,25]; (ii) identification of factors (sources) controlling water quality [17,21,23,24,25,26,27]; and (iii) revealing of spatial–temporal variations in the investigated water body [20,21,22,27,28]. Additionally, multivariate statistical results could be used for the optimization of water quality monitoring programs by revealing existing patterns of water quality indicators and sampling sites.…”
Section: Introductionmentioning
confidence: 99%
“…found that the Canadian Council of Ministers of the Environment Water Quality Index CCME WQI is the strictest among the considered methods [5]. The CCME WQI method was considered by various researchers and a fair description can be found in [5,6,7,8]. Some of the issues that occur when dealing with measurements are given in [9,10].…”
Section: Introductionmentioning
confidence: 99%